2010
DOI: 10.1016/j.jvs.2010.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes after Acute Pulmonary Embolism: A Pooled Survival Analysis of Different Adverse Events

Abstract: A number of studies have linked chronic exposure to infectious agents such as Helicobacter pylori, Chlamydia pneumoniae, and herpes viruses to coronary artery disease and stroke (Wimmer MLJ, et al [Stroke 1996;27:2207-10] and Ridker PM et al [Circulation 1998;98: 2796-2799) with atherosclerosis. It has been thought that chronic infections may lead to an inflammatory process through remote signaling of inflammatory mediators that ultimately begin the process of atherosclerosis. The authors postulate that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 0 publications
1
59
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] A recent study reported an 8-year mortality risk of 12%, 1 whereas in an earlier study, mortality risk reached 50% after 8 years of follow-up. 5 Previous studies were limited by short follow-up time (maximum, 10 years), [1][2][3][4][6][7][8][9][10][11] age restrictions (<70 years of age 1 or between 65 and 89 years of age 7 ), lack of adjustment for comorbidity 3,12 or calendar period, 3,5 and failure to examine mortality for DVT and PE separately. 1,8,12 Only a few studies have compared long-term mortality between VTE patients and a comparison cohort from the general population, with inconsistent results.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] A recent study reported an 8-year mortality risk of 12%, 1 whereas in an earlier study, mortality risk reached 50% after 8 years of follow-up. 5 Previous studies were limited by short follow-up time (maximum, 10 years), [1][2][3][4][6][7][8][9][10][11] age restrictions (<70 years of age 1 or between 65 and 89 years of age 7 ), lack of adjustment for comorbidity 3,12 or calendar period, 3,5 and failure to examine mortality for DVT and PE separately. 1,8,12 Only a few studies have compared long-term mortality between VTE patients and a comparison cohort from the general population, with inconsistent results.…”
mentioning
confidence: 99%
“…Platelets and markers of platelet [62,63]. The combined results of two randomized, double-blind trials, WARFA-SA and ASPIRE, showed that aspirin, compared with placebo, reduced the rate of recurrence to 32 % (P = 0.007) in patients with a fi rst unprovoked VTE who had completed at least six months of standard therapy, without increased risk of major bleeding [64,65].…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…VTE is characterised by a persistent higher mortality, leading to 6-12 % of deaths within one month from the diagnosis and a yearly rate of mortality up to 8.5 % in patients aff ected by PE [2].…”
Section: Introductionmentioning
confidence: 99%
“…While many patients recover completely after acute pulmonary embolism (PE), some go on to develop serious cardiopulmonary disabilities (1). PE that fails to resolve can be remodeled into progressive intravascular scars that cause persistent lung perfusion defects, which some have called chronic thromboembolic disease.…”
mentioning
confidence: 99%